COMPARISON OF URBAN DEVELOPMENT PATTERNS BASED ON LAND CAPABILITY UNITS (LCU) IN THE TALIWANG URBAN AREA - Fariz Primadi Hirsan; Sri Rahmi Yunianti; Armei Rapudin (Universitas Sebelas Maret (UNS), 2026)
Taliwang Urban Area, the capital of West Sumbawa Regency, functions as the administrative and socio-economic center of the region and has experienced rapid urban growth over the past decade. Data from the Regional Development Planning Agency (Bappeda) indicate that built-up land expanded by nearly 35% between 2014 and 2024. While this growth reflects dynamic development processes and the implementation of spatial planning policies, expansion into areas with low environmental carrying capacity increases the risk of environmental degradation and disaster vulnerability. This study examines the relationship between land capability and urban development patterns using the Land Capability Unit (LCU) approach. A descriptive analytical method with a spatial framework was applied, employing overlay analysis and thematic map interpretation. The findings reveal that although 51% of Taliwang District is situated within zones of relatively high land capability, significant urban expansion has occurred in areas with low land capability. This spatial inconsistency may lead to inefficient land use and heightened environmental risks. The study emphasizes the importance of land suitability–based planning that prioritizes biophysical characteristics to support sustainable urban development and disaster risk reduction.